Kualitas Pelayanan Publik Di Kantor Desa Parigi Kecamatan Tinggimoncong Kabupaten Gowa - Musdalipa Musdalipa; Anwar Parawangi; Ihyani Malik (Department of Public Administration, Muhammadiyah University of Makassar, 2017)
The aim of the study is to find out how the quality of Public Service at the Parigi village office, District Tinggimoncong, Gowa. The research method used was a qualitative descriptive study. There were 16 informants and the data were collected through interview, observation, and documentation. The technique of data analysis was conducted through the stages of data reduction, data presentation and data verification. The results of the research showed that generallythe quality of public services at the village office of Parigi, District Tinggimoncong,Gowabased on the five indicators, namely, tangible, reliability, responsiveness, assurance, and empathy was still less qualified, as well as the apparatus of Parigi village should further improve theservice quality again to increase the ability and motivation, and the most important thing is disciplineKeywords: quality, service Penelitian ini bertujuan untuk mengetahui bagaimana Kualitas Pelayanan Publik Di Kantor Desa Parigi Kecamatan Tinggi moncong Kabupaten Gowa. Metode penelitian yang digunakan adalah jenis penelitian deskriptif kualitatif. Informan berjumlah 16 orang dengan menggunakan teknik pengumpulan data melalui wawancara, observasi dan dokumentasi. Teknik analisis data penelitian melalui tahapan reduksi data, penyajian data, dan verifikasi data. Hasil penelitian ini menunjukkan bahwa umumnya kualitas pelayanan publik di Kantor Desa Parigi Kecamatan Tinggi Moncong Kabupaten Gowa yang di lihat dari lima indicator yaitu, berwujud, kehandalan, ketanggapan, jaminan, dan empati masih kurang berkualitas. Begitupun aparatur Desa Parigi harus lebih meningkatkan kualitas pelayanananya lagi dengan meningkatkan kemampuan dan motivasi yang paling utama kedisiplinan. Kata Kunci : Kualitas, Pelayanan